Using simulation to prepare neophyte nursing students to deliver intimate patient care. Issue 2 (April 2019) - Reid-Searl, Kerry; Mainey, Lydia; Bassett, Jenny; Dwyer, Trudy
Abstract: Background: Preparing neophyte nursing students to deal with the intimate aspects of patient care including nudity and body excretions is challenging. Traditional simulation approaches that have been used to teach these skills require examination in the context of considering more realistic ways. Mask-Ed™ is a high fidelity modality of simulation that enables the educator to transform into a patient by donning silicone props such as masks and body torsos inclusive of genitalia. The hidden educator is able to coach and direct the learner throughout the simulation. Aim: The aim of this study was to identify if Mask-Ed™ simulation enhanced students learning in the context of providing intimate patient care when undertaking the skills of showering and toileting. Methods: First year undergraduate nursing students were tasked with showering and toileting a Mask-Ed™ patient in a simulated learning situation within a laboratory context. Following the simulation students were invited to participate in focus groups. Data was recorded, transcribed and analysed using an inductive thematic analysis approach. Findings: From class preparation to debrief, participants experienced a safe journey of discovery enabling them to provide intimate care. The realism of the learning environment combined with the confidence students had in their educator, allowed students to overcome their nervousness and anxiety, discover the vulnerable person at the centre of their care, gain confidence and find comrades. Discussion: Simulations that provide neophyte nursing students with an opportunity to face real to life intimate care experiences should be apparent in all undergraduate nursing programs. Nursing students need not only to be prepared to implement skills around safe practice when showering and toileting patients but they also need to feel safe and confident to practice themselves. Conclusion: Mask-Ed™ is an effective and efficient simulation modality to teach neophyte nursing students about intimate human care.